Editorial - Remco Veltkamp (Serious Games Society, 2016)
I am very pleased to introduce this special issue of IJSG, which is  dedicated to the Games and Learning Alliance Conference (GaLA Conf), that was held in Rome, December 2015. A number of the best conference papers were selected, and the authors were invited to extend their paper with at least one third new content, and to submit their paper to IJSG to undergo a regular review process. This issue contains five of these papers.